Hypoglycemic effect of poly-herbal combination in streptozotocin-induced diabetic rats (Bangladesh Journal of Pharmacology, 2016)
The present study evaluates the combinatorial effect of a poly-herbal combination with multiple therapeutic effects as a hypoglycemic and hypolipidemic agent. Herbal combination of Salacia oblonga, Tinospora cordifolia, Emblica officinalis, Curcuma longa and Gymnema sylvestre was prepared and administered to streptozotocin (55 mg/kg, i.p.)-induced diabetic rats, at a dose of 100 mg/kg, for four weeks. The poly-herbal combination significantly elevated the plasma insulin (90%) and reduced serum glucose (42%), cholesterol (49%), triglycerides (43%), LDL cholesterol (62.5%) and plasma apo B/apo A in the diabetic rats. The liver lipogenic enzymes like HMG CoA reductase and glucose-6-phosphatase significantly declined (p